ONCE MORE ABOUT ANTONIA TRYPHAINA - Victor Cojocaru (Journal of Ancient History and Archaeology)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">As a king<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">’s daughter, a king’s wife and the mother of kings, Antonia Tryphaina played a major role in the kinship ties of the ruling circles in the Julio-Claudian period. Although her name did not go unnoticed in scholarly literature, this great-granddaughter of M. Antonius has quite undeservedly been regarded as a historical figure of secondary importance. Besides, her treatments tend to show by numerous inaccuracies and much speculation. The author therefore felt that a new investigation was required, though he unexpectedly found himself involved in a more complex scrutiny than previous studies had let him foresee.